A Comparative Analysis of Classical and Contemporary Integrative Methodologies in Islamic Education Studies - Hayat, Ade Putra; Charles, Charles (El-Rusyd, 2025)
This study examines the fundamental issue of epistemological tension as well as the potential for synergy between classical integrative methodology and contemporary integrative methodology in the study of Islamic education. The purpose of this study is to analyze in depth the similarities, differences, and potential synthesis of both approaches as an effort to construct a relevant paradigm of Islamic education in the modern era. The research was conducted using a qualitative method with a content analysis approach and comparative analysis. The results indicate that classical integrative methodology is rooted in the concept of wahdat al-‘ilm with a theocentric orientation, whereas contemporary integrative methodology is dialogical, multidisciplinary, and responsive to the development of modern scientific knowledge. A new finding of this study is the importance of reconstructing a methodology that not only preserves the values of tawhid but also promotes social transformation and scientific innovation. The main conclusion of this study is that a synthesis of the two is necessary to produce a transformative-integrative model that is relevant to the needs of Islamic Higher Education Institutions in the era of globalization. These findings are significant for the development of curricula, educational policies, and interdisciplinary research oriented toward forming individuals who are holistic, critical, productive, and contributive.